Sonicating for the Uptake of Paracetamol from Solution by Activated Carbon from Oak: Kinetics, Thermodynamics, and Isotherms - Alaa M. Al-Ma’abreh; Gada Edris; Mike Kh. Haddad (Adsorption Science & Technology, 2023)
This inquiry used ultrasonic waves to uptake paracetamol (PA) by using oak-based activated carbon (ACO). The surface of ACO was explored based on FT-IR, SEM, and XRD before and after the adsorption. The kinetic data for PA adsorption onto ACO corresponds to a pseudo-second-order kinetic model. Isothermal models of the Langmuir, Freundlich, D-R, and Temkin were used. The adsorption of PA onto ACO was found to be a monolayer with 96.03% uptake, which corresponds to Langmuir. The thermodynamic experiments revealed the endothermic nature of PA adsorption onto ACO. Under the investigated optimal conditions, the adsorption capacity of PA onto ACO was found to be 97.1 mg. L-1. ACO could be recycled after six regenerations. Ultimately, sonicating has adequate performance for the uptake of PA by ACO.